Assessing the feasibility of gray, blue, and green ammonia productions in Indonesia: A techno-economic and environmental perspective - Martin Tjahjono; Isabella Stevani; Gracheilla A Siswanto; Arief Adhitya; Iskandar Halim (International Journal of Renewable Energy Development, 2023)
Ammonia, owing to its carbon-free attributes, stands as a promising alternative for replacing fossil-based fuels. This study investigates the techno-economic and environmental aspects of gray, blue, and green ammonia production in Indonesia. In this regard, a spreadsheet-based decision support system has been developed to analyze the levelized cost of each mode of ammonia production and their cost sensitivity across various parameters. The results of the analysis show a levelized cost of gray ammonia of $297 (USD) per ton, which is strongly affected by natural gas prices and carbon taxation. Blue ammonia emerges as the most stable production option with a levelized cost of $390 per ton, impacted by natural gas prices and the expenses associated with carbon sequestration. On the other hand, the levelized cost of green ammonia varies between $696 to $1,024 per ton and is predominantly influenced by the choice of electrolyzers, the cost of renewable energy sources, and maintenance and operational expenditures. Furthermore, the study reveals that gray and blue ammonia production result in emissions of 2.73 and 0.28 tons of CO2 equivalent per ton of ammonia, respectively, while in-situ carbon emissions from green ammonia can be considered negligible. Overall, this study underscores the potential of implementing green ammonia production utilizing geothermal or hydropower renewable energy resources as viable solutions for decarbonizing the power, industry, and transport sectors in Indonesia. Several policy recommendations aimed at overcoming existing barriers to the development of green ammonia plants in the country are also provided.